Approaches for effective using of interline power flow controller steady state model - A. Hussein, Nabil; A. Eisa, Ayamn; M. Mahmoud, Hassan; A. Shehata, Safy; A. Othman, El-Saeed (International Journal of Engineering and Technology, 2018)
Interline power flow controller (IPFC) is the latest proposed flexible alternating current transmission systems (FACTS) device. Although IPFC was proposed in 1998, its performance studying stills good research area. It cannot be denied that, the first step for performance anal-ysis is developing an effective simulation model. This paper is tackling; the steady state modeling for a power system equipped with IPFC device, approaches for applying this model and the idea behind each approach. 5-Bus, 14-Bus and 30-Bus systems have been chosen as case studies to support the comparison between the three approaches.Â Â